Human rights in a posthuman world critical essays - Baxi, Upendra (Delhi ; Oxford : Oxford University Press, 2009)
This book, which the author describes as a sequel to 'The Future of Human Rights', is an analysis of the state of human rights in a 'post human' and 'machinistic' world facing unprecedented security concerns, 'terrorist threats', and technoscience.
Originally published: 2007.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human rights